STRATEGY FOR MAINTAINING THE EXISTENCE OF THE FARISA CRAFT BUSINESS IN DUKUH VILLAGE, GONDANG DISTRICT, TULUNGAGUNG DISTRICT - Dewi, Rohma Aliska; Suryaningsih, Tutut (Universitas Negeri Yogyakarta, 2023)
Responding to the increasingly stringent developments in the business world, entrepreneurs must plan the right strategy so that their business continues to exist. The purpose of this research is to find out how the strategy of the